Understanding Enabling Factors for Community-Led Coral Reef Health Monitoring and Early Warning System through Participatory Action Research - Eni Hidayati; Mahardika Rizqi Himawan; Edwin Jefri (LPPM Universitas Mataram, 2023)
Coral reefs are under pressure from climate change and various factors, putting them at risk of a decline in resilience. This heightened vulnerability increases the likelihood of reaching a tipping point with the next shock or stressor. Identifying early warning indicators for tipping points is crucial for proactive coral reef management. Therefore, this study aims to comprehend the coral reef health parameters considered important and feasible for collection by local stakeholders, as well as identify factors facilitating the implementation of a community-based monitoring and early warning system in a fishers-dominated community. The approach used was Participatory Action Research. The results reveal twelve priority parameters deemed necessary by the local community and feasible for collection by local stakeholders, including the local community, university, and non-governmental organization. The identified parameters are: coral bleaching, visibility, temperature, pH, dissolved oxygen, salinity, current, coral percent cover, fish community, macroalgal canopy cover and composition, benthic composition, and plankton. Interpretive structural model and MICMAC analysis show nine enabling factors supporting the development of a community-led coral reef health monitoring and early warning system. These factors include team motivation, training and team capacity, connection with government, connection with university, facilitation by NGOs, supporting regulations, operational funds, access to equipment, and operation and maintenance of equipment. Team motivation stands out as the most influential factor, with strong driving power and dependence, making it crucial to manage as actions on it will have ripple effects on other factors.